Peranan agensi-agensi pertanian dalam penamaan padi di Kedah,1970-1990 - Veronica Anak Arun (Tanjong Malim, 2023)
Peranan agensi-agensi pertanian dalam penamaan padi di Kedah,1970-1990 by Veronica Anak Arun